Reassessing dubbing historical approaches and current trends - Ranzato, Irene; Zanotti, Serenella (Benjamins translation library,, 2019)
"Despite a long tradition of scholarship and the vast amount of dubbed audiovisual products available on the global market, dubbing is still relatively underrepresented in audiovisual research. The aim of this volume is to give dubbing research its due by showing that, far from being a doomed or somewhat declining form of AVT, it is being exploited globally in the most diverse and fruitful ways. The contributions to this collection take up the diverse strands that make up the field, to offer a multi-faceted assessment of dubbing on the move, embracing its important historical past as well as present and future developments, thus proving that dubbing has really come a long way and has not been less ready than other AVT modes to respond to the mood of the times. The volume will be of interest for scholars and students of translation studies, audiovisual translation, linguistics, film, television and game studies"--